The textbook of pharmaceutical medicine - Griffin, J. P. (John Parry); Posner, John.; Barker, Geoffrey R. (Chichester, West Sussex [U.K.] : Wiley-Blackwell : BMJ Books, 2013)
Now in its seventh edition, The Textbook of Pharmaceutical Medicine is a standard reference for all those working in pharmaceutical medicine and the recognised text for the UK Faculty of Pharmaceutical Diploma. This new edition reflects the enormous changes in the environment in which the pharmaceutical industry and the pharmaceutical physician operate, many of which have occurred since 2009 when the last edition was published. There are new chapters and new authors in each section, and more consideration given to ethical issues across all areas of the book.
pt. 1. Research and development -- pt. 2. Regulation -- pt. 3. Health care marketplace.
Includes bibliographical references and index.
Online resource; title from home title page (Wiley, viewed on May 24, 2013).
Keywords: Drug approval; Pharmacology; Clinical trials; Drug Approval; Clinical Trials as Topic; Pharmacology; Pharmacology, Experimental; Pharmacology; MEDICAL -- Drug Guides; MEDICAL -- Nursing -- Pharmacology; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy; Clinical trials; Drug approval; Pharmacology; Electronic books